A study on the factors influencing firms leverage performances - Mohd Safni, Nur Hanis (2011)
There are many research have been conducted in order to investigate the relationship effects of the leverage performance towards stock price movement. This study is attempt to extend the body of knowledge by analyzing the factors that influence the leverage performance of the company by using industry, firm size and inflation rate in Malaysian market as the independent variables. The Single Linear Regression (SLR) and Multiple Linear Regression (MLR) approaches have been applied to measure the significant relationship between industry, firm size, inflation rate and leverage performance from 2005 until 2009. The result shows that all the variables have a significant relationship with the leverage performance in Malaysian market. Thus, the result from this research has some potential to be used by the market analyst for predicting stock price movement of the chosen company in this country based on the firms leverage performances.